How well do we understand sovereign debt crisis? Evidence from Latin America - Maximilian Ludwig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In recent years, the number of theoretical models on sovereign default exploded. I take a step back and investigate how good our current theoretical understanding of real world sovereign debt crisis really is. This is done by deriving implications that are hard wired into our models and comparing the evolution of nearly 20 sovereign debt crises in Latin America with them. I find that the available models capture aspects of virtually all crises, yet there are only a few crisis that are fully consistent with the available models.
Keywords: E65; F34; H63; 330